2012
DOI: 10.1007/s11695-012-0782-1
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Mid-Term Results of Conversion from Sleeve Gastrectomy to Roux-en-Y Gastric Bypass

Abstract: Sleeve gastrectomy (SG) is currently considered as a primary bariatric surgery. This is because of its relative simplicity and satisfactory results. As observed with other bariatric procedures, surgeons are confronted with insufficient weight loss or weight regain, insufficient resolution of metabolic disorders, and intractable severe reflux. A retrospective analysis of conversion from SG to Roux-en-Y gastric bypass (RYGBP) was performed to assess weight loss, diabetes resolution, and relief of reflux symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 22 publications
3
39
0
2
Order By: Relevance
“…The present study showed a significant decline in body mass index, waist circumference, and fat percent among patients undergone gastric sleeve surgery with a significant differences between patient and controls which is agreed by Gautier T et al (13)indicated that weight loss was significantly improved after bariatric surgery (mean loss percentage of excess of body weight, 64.6 % versus 47.1 %) and all reflux symptoms are eliminated without any medication at the end of the follow-up. Several studies have demonstrated that the amelioration of metabolic dysfunction is attributable not only to weight loss and caloric restriction, but also to endocrine changes resulting from surgical manipulation of the gut.…”
Section: IVsupporting
confidence: 90%
“…The present study showed a significant decline in body mass index, waist circumference, and fat percent among patients undergone gastric sleeve surgery with a significant differences between patient and controls which is agreed by Gautier T et al (13)indicated that weight loss was significantly improved after bariatric surgery (mean loss percentage of excess of body weight, 64.6 % versus 47.1 %) and all reflux symptoms are eliminated without any medication at the end of the follow-up. Several studies have demonstrated that the amelioration of metabolic dysfunction is attributable not only to weight loss and caloric restriction, but also to endocrine changes resulting from surgical manipulation of the gut.…”
Section: IVsupporting
confidence: 90%
“…Langer et al reported the conversion of 8 patients from LSG to LRYGB with a mean weight reduction of 15.2 ± 8.0 kg at a mean follow-up duration of 33 months [22]. Gautier et al reported on 18 patients who were converted to RYGB for different indications and illustrated effective weight loss results [23]. In summary, only a few studies documented outcome data for more than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The Roux-en-Y loop avoids biliary reflux and exerts a downward pulling effect that retains the gastric pouch into the abdomen. For these reasons, when doing a conversion from LSG into RYGB [42], the pouch must be resized and any persistent gastric fundus has to be resected [43]. The hiatus should be carefully inspected for the presence of hiatal hernia as we found that in the long term the latter may be responsible for the migration of the gastric pouch into the thorax, although this condition may cause dysphagia which requires surgical treatment [44].…”
Section: Gerd Complicating Sleeve Gastrectomymentioning
confidence: 99%